(untitled) (Contemporary Mathematics, 2024)
In this work, a co-variational inequality problem and a co-resolvent equation problem are introduced and investigated. It is shown that the fixed point problem is equivalent to the problem of co-variational inequality. The co-variational inequality problem and the co-resolvent equation problem are equivalent due to this resemblance. The coresolvent equation problem is solved using an iterative approach that we provide at the final stage. Our findings may be seen as an enhancement of several established findings.